A possible characterization of the homoeopathic effect - Vega, Guadalupe Ruiz; Torres, José-Leonel (British Homeopathic Journal, 1997)
Electrical signals from a photoelectric plethysmograph are used to test peripheral blood circulation as a source of a homoeopathically relevant parameter that will vary in a reproducible and systematic way following exhibition of specific medicines in homoeopathic doses. Mathematical treatment of the signals gives a Fourier power spectrum with an approximately linear profile (in a log-log plot) at the lowest frequencies. The gradient of this line seems to meet the above requirements of reproducible and systematic variation under a homoeopathic stimulus, and this is our basis to propose an analogous treatment for other electrical signals from the body, especially those from the heart and brain.